Formação inicial de professores e educação de jovens e adultos: possibilidades da extensão universitária - Dall'Acqua, Maria Júlia Canazza [UNESP]; Vitaliano, Célia Regina; Carneiro, Relma Urel Carbone [UNESP] (My University, 2013)
The present work aimed at investigating the possibilities and limits of academic extension programs as an environment for initial teacher learning and training. It also focused on investigating the main difficulties identified by Pedagogy and Social Science students about this initial training regarding its use in actual teaching activities. It focused on undergraduate students’ perceptions concerning their involvement in an academic extension project which enabled them to interact with students as teachers in a Youth and Adult Education program, during a whole academic year. Semi-structured interviews were done with nine participants. The content of these interviews was analyzed and divided into four thematic categories. The results show that, for these students, what makes this kind of project unique is the possibility of acting in real situations, under supervision, which provided a moment for reflection. Focusing on supervision, the students point out that this resource is not usually there in traditional internship situations – and that they consider it an important and necessary aspect. It was also indicated the relevance of practice, self-awareness and teaching activity experiences. In conclusion, it was perceived that academic extension programs must be more intensively appreciated, given the coordinating role it can play between investigative and didactic activities, both key to initial training.

O trabalho que aqui se apresenta teve como objetivo investigar possibilidades e limites da extensão universitária como ambiente de aprendizagem e formação inicial de professores, propondo-se também a analisar as principais dificuldades identificadas por alunos dos cursos de Pedagogia e Ciências Sociais (licenciatura) acerca dessa formação inicial para o exercício da atividade docente. Focaliza as percepções de graduandos em relação à participação em um projeto de extensão que lhes possibilitou atuar como professores de alunos em sala de aula da Educação de Jovens e Adultos (EJA), durante um ano letivo. Foram realizadas entrevistas semi-estruturadas com nove participantes. O conteúdo das falas foi analisado e organizado em quatro categorias temáticas. Os resultados mostram que, para esses graduandos, o diferencial da extensão universitária é que a mesma oferece a oportunidade de atuação numa situação real, porém sob supervisão, evidenciando um espaço de reflexão originada na prática. Dando ênfase à supervisão, os alunos valorizam esse recurso como relevante e mencionam ser justamente ele que não está presente de forma habitual nas situações tradicionais de estágio. Destacam também a relevância da prática, da autopercepção e da vivência do fazer docente. Concluindo, percebe-se que os dados são indicativos de que, com pouca visibilidade no contexto acadêmico, atividades extensionistas necessitariam ser mais e intensamente valorizadas, dado o papel articulador que podem exercer entre as atividades investigativas e didáticas, essenciais para a formação inicial.
Initial teacher training and youth and adult education: academic extension possibilities
Keywords: Academic extension; Initial training; Teaching; Extensão universitária; Formação inicial; Docência